Advancements in Metallurgical Processes for Machinery Production - Tuxliyev Muslimbek Sherzod o’g’li (Scientific Trends, 2025)
This study highlights recent advancements in metallurgical processes and their impact on machinery production. Key areas include casting, thermal treatment, and pressure-based metal processing, as well as the role of novel alloys in improving durability and efficiency. The research employs a combination of experimental and analytical methods, resulting in innovations that enhance production precision, reduce costs, and extend component lifespans. These findings underscore the transformative potential of modern metallurgy in technical fields.
Keywords: Metallurgy, casting techniques, thermal treatment, pressure processing, novel alloys, machinery production, material science.